ANALISIS FAKTOR UNTUK PEMBENTUKAN INDEKS KESEHATAN IBU DI PROVINSI KALIMANTAN SELATAN - Noorsa'adah Noorsa'adah; Nur Salam; Dewi Anggraini (RAGAM: Journal of Statistics & Its Application, 2023)
Maternal health is an important health problem because mothers are the printers of the next generation. Maternal health can describe the quality of the child to be born, so maternal health is very important to pay attention to. In Indonesia, the government has made various efforts to improve maternal health, which is still far from being expected. In this improvement effort, it is necessary to have a measure that can be used to monitor and evaluate the health development carried out, especially in the Province of South Kalimantan. Therefore, this study aims to establish a measure that can be used to describe maternal health through a composite index approach. The formation of the composite index is carried out using a technique offered by the Organization for Economic Co-Operation and Development (OECD), namely using factor analysis. Factor analysis was conducted to reduce indicators that were not significant in describing maternal health. Furthermore, the composite index formed is used to group districts/cities to make it easier to set priorities for maternal health development in South Kalimantan Province. Based on factor analysis results, the final indicators used to form the maternal health index amounted to 24 of the 30 initial indicators. After that, from the formation of the maternal health index using the composite index, it was found that the best maternal health was dominated by the cities of Banjarbaru and Banjarmasin. Meanwhile, the worst maternal health index is in Hulu Sungai Selatan District. Keywords:  Maternal Health , Composite Index, Factor Analysis.